Antecedents Sensory Appeal And Consequences It Recommend Intention, Revisit Intention, Willingness To Buy Culinary Product - Juliana Juliana; Amelda Pramezwary; Arifin Djakasaputra; Jimmy Muller Hasoloan Situmorang; Nova Bernedeta Sitorus; Fachrurazi Fachrurazi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The goal of this study was to see if Cultural Experience, Excitement, Health Concern, and Sensory Appeal had an effect on Recommendation Intention, Recurrence Intention, and Willingness to Buy Culinary Product. This study's population consists of tourism tourists who visit Medan City's culinary tourism. This study's sample size was 200 people. This is a quantitative study using a survey method. In this study, a questionnaire was used to collect data. Domestic tourists who visited Medan City culinary tourism were distributed online questionnaires to respondents using a Non Probability Sampling approach using purposive sampling with the criteria that tourists had visited Medan City culinary tourism once a year. PLS-SEM is used to analyze data. The findings revealed that Cultural Experience, Excitement, and Health Concern variables had a positive influence on Sensory Appeal, and Sensory Appeal variables had a positive influence on Recommend Intention, Revisitation Intention, and Willingness to Buy Culinary Product.